Development and strengthening of emotional competencies in early childhood education in Ibero-America: a systematic review - Simeón-Aguirre, Erika E. (2021)
The objective of this review was to provide the current status regarding empirical studies on the development and strengthening of emotional competencies in the field of early childhood education at the Ibero-American level, which were extracted from journals indexed in the databases Scopus, EBSCO, Dialnet and SciELO between the years 2010 to 2019. The analysis of the reviewed articles includes aspects such as: (a) Emotional competencies in increasing positive attitudes of educational actors, (b) the value of knowledge and emotional regulation for the best student development and teacher professional development, and (c) the importance of studies and educational programs based on the development and strengthening of emotional competencies that optimize pedagogical management and the classroom climate. The results regarding the number of publications reviewed show an ascending nature, with Spain being the country with the highest number of publications on the subject. Within the identified methodology, it was found that most of the publications were quasi-experimental and pre-experimental studies that generated significant effects on the emotional competencies of students and / or teachers. In conclusion, according to the articles reviewed, the development and strengthening of the emotional competencies of the students and / or teachers of early childhood education was favorable through the application of programs in the Ibero-American countries; as well as other studies demonstrated the high degree of relationship of these competences with other relevant aspects in the training of the student and in the work of the teacher.